2013
DOI: 10.1016/j.jpainsymman.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Advanced, Progressive, Recurrent Cancer: A Randomized Controlled Trial

Abstract: This intervention significantly reduced the unmet needs of cancer survivors and it is likely that it is cost-effective. Despite small numbers, the main effect size was robust. We recommend implementation alongside evaluation in wider clinical settings and patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 24 publications
(12 reference statements)
0
66
1
1
Order By: Relevance
“…A recent randomized clinical trial in patients at the end of treatment for advanced recurrent hematologic or breast cancer showed that a rehabilitation intervention delivered by a multidisciplinary team in combination with usual care was superior to usual care alone in reducing psychological, physical, and patient care needs and in improving the patient's self-reported health state 16 . The intervention was tailored to the patient and lasted approximately 3 months, but it was not clear which health professionals constituted the care team and which specific interventions they provided.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized clinical trial in patients at the end of treatment for advanced recurrent hematologic or breast cancer showed that a rehabilitation intervention delivered by a multidisciplinary team in combination with usual care was superior to usual care alone in reducing psychological, physical, and patient care needs and in improving the patient's self-reported health state 16 . The intervention was tailored to the patient and lasted approximately 3 months, but it was not clear which health professionals constituted the care team and which specific interventions they provided.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy and exercise have been shown to be a feasible modality for terminally ill patients [62], and patients who participated in a specific combination palliative rehabilitation program did show improvement in physical performance and symptom severity [63]. Rehabilitation services provided in a hospice day care unit for individuals with advanced, recurrent, or progressive breast or hematological malignancy also showed significant reduced need for health service resources along with corresponding improvement in QOL [64]. Furthermore, early integration of palliative care in the oncology care continuum may result in particularly meaningful healthcare cost reductions, as this approach improved both survival rates and QOL [65].…”
Section: Advancing Collaborative Interdisciplinary Care Coordinationmentioning
confidence: 99%
“…34 Another trial shows that rehabilitation in a hospice day care unit reduced the unmet needs for psychological support for patients with advanced, recurrent, or progressive cancer. 35 Future intervention studies are needed to investigate the most optimal means to improve care for patients with recurrent cancer and to overcome barriers to integration of palliative care. 36,37 In contrast to earlier studies and to our hypothesis, our study indicated that having a recurrence does not change overall satisfaction with information provision.…”
Section: Discussionmentioning
confidence: 99%